Yellowstone cougars: ecology before and after wolf restoration - Ruth, Toni K., author; Boutte, Polly C., author; Hornocker, Maurice G., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2019)
Examines the effect of wolf restoration on cougar population in Yellowstone National Park. No other study has addressed theoretical and practical aspects of competition between large carnivores. A thorough examination of cougar ecology, how they interact and are influenced by wolves, how this knowledge informs management and conservation.--Provided by publisher.
The northern Yellowstone landscape -- Quantifying how species compete or coexist -- Predation on the Greater Yellowstone Northern Range -- Prey selection by cougars and wolves -- Rates of predation -- Direct interactions at kills -- Combined influences: cougars, wolves, and humans -- How might cougars respond to wolves? -- Spatial responses of cougars to wolf presence -- Patterns of resource use prior to and during wolf restoration -- Synthesis: competition refuges and managing risks in a wolf-dominated system -- Before and after wolf restoration: cougar population characteristics. How might wolf restoration affect the cougar population? -- Cougar population structure -- Reproduction and survival rates of cougars -- Dispersal and population change -- Synthesis: the niches of cougars and wolves -- Management and conservation of cougars: considering interspecific competition.
Keywords: Puma -- Ecology -- Yellowstone National Park; Wolves -- Ecology -- Yellowstone National Park; Wolves -- Reintroduction -- Yellowstone National Park; Predation (Biology) -- Yellowstone National Park; Competition (Biology) -- Yellowstone National Park; Wildlife management -- Yellowstone National Park